Fernand of Spain and His Question on Whether Prime Matter Can be Denuded of Any Dispositions Prior to Introduction of Substantial Form.: Sententia Metaphysicae XII, qu. Unica (Cambridge, Peterhouse 56 III, ff. 159va–161rb) - Tomanek, Łukasz (Przegląd Tomistyczny, 2025)
This article is an introduction to and a critical edition of an excerpt from a commentary on the Metaphysics, written by the 13th-century Parisian master Fernand of Spain (fl. 1281–1302 †). The question critically edited in this article, Utrum forma substantialis introducatur in materia ut est nuda ab omnibus accidentibus et dispositionibus praecedentibus formam in materia, concerns the nature of a physical body as a composite of matter and form and as a mixt of simple bodies, i.e., elements. On this occasion, Fernand stresses the importance of the correct reading of Aristotle’s doctrine of prime matter — a reading that is substantially influenced by Averroes’ notion of indeterminate dimensions that inhere in prime matter. Following the subject of the question, the article addresses the interpretative principles that Fernand endorses while commenting on Aristotle. It also discusses the extensive use of Averroes’ works in Fernand’s exposition of the Aristotelian doctrine of material substance.